COMPETITION EFFECT ON THE WORDS VISUAL RECOGNITION WITH MASKED PRIMING TASK: A PSYCHOPHYSIC APPROACH - Perea, Manuel; Rosa, Eva (Anales de Psicología / Annals of Psychology, 2000)
One of the most central issues in cognitive psychology is how the processing of a given word is affected by its similarly spelled words (the so-called “orthographic neighbors”). In the present study, we analyzed how the magnitude of orthographic/repetition priming (e.g., tigus- TIFUS and tifus-TIFUS) is modulated by the number of neighbors of a target word. We used the masked priming technique (Forster & Davis, 1984) at a 33 ms stimulusonset asynchrony (SOA) in the lexical decision task. Because of the very brief SOA, a psychophysical methodology (i.e., few but well-trained participants) was adopted. Activation-based models predict greater orthographic/ repetition effects for the words with few neighbors, whereas the entry-opening model (Forster & Davis, 1984) predicts an interaction between number of neighbors and orthographic (but not repetition) priming. The results show greater repetition/orthographic priming effects for hermit words than for words with many neighbors, which is consistent with an activation account. Finally, we examine the advantages of using a psychophysical methodology combined with the masked priming technique.